2012
DOI: 10.1155/2012/682156
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Diet and Tobacco Smoking on Pancreatic Cancer Incidence in Poland in 1960–2008

Abstract: The aim of the study was to investigate the relationship between pancreatic cancer incidence and selected dietary factors, alcohol consumption, and tobacco smoking in Poland in 1960–2008. Data on pancreatic cancer morbidity were derived from the National Cancer Registry and on food consumption from the national food balance sheets. In 1960–1989 correlations were found between pancreatic cancer incidence rates and energy (0.60 for males and 0.57 for females), cholesterol (0.87 and 0.80), fibre (−0.84 and −0.89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…plays a role in the development of pancreatic cancer[25,26]. In addition, the highest rates for pancreatic cancer mortality in eastern European countries suggested that other factors (including prevalence of diabetes, obesity, alcohol use) could influence the mortality of pancreatic cancer[27]. …”
Section: Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…plays a role in the development of pancreatic cancer[25,26]. In addition, the highest rates for pancreatic cancer mortality in eastern European countries suggested that other factors (including prevalence of diabetes, obesity, alcohol use) could influence the mortality of pancreatic cancer[27]. …”
Section: Mortalitymentioning
confidence: 99%
“…However, the recent increasing trends in some countries in the European Union suggest that other factors (including mainly obesity, physical inactivity, diabetes, and dietary factors), besides smoking, may have influenced the pancreatic cancer mortality[20,22,31,33]. In recent years, people in developing countries adopt lifestyles and behaviors that are typical for developed countries, such as cigarette smoking, higher consumption of saturated fat and calorie-rich foods, and reduced physical activity[25,27,34]. Besides, the trends might be due to disparities in socioeconomic circumstances between high- and low-income areas.…”
Section: Temporal Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in Aoun et al study, they said the main risk factors of lung cancer among Lebanese women are use of heating fuel and cigarette smoking [32]. Pancreatic cancer is a rapidly fatal disease; it's associated with tobacco smoking [33]. In Hosseini M et al study, he reports that shisha smoking is one of the risk factors for prostate cancer [34].…”
Section: Association Of Wps With Cancermentioning
confidence: 99%
“…Among the unchangeable factors are: age, sex, ethnicity, blood group 0 (I), diabetes mellitus (DM), hereditary predisposition, genetic disorders. The risk factors that can be corrected are obesity, smoking, alcohol abuse, chronic pancreatitis, Helicobacter pylori infection [4,5].…”
mentioning
confidence: 99%